LEARNING DIFFICULTIES OF CHILDREN WITH SPECIAL NEEDS SLOW LENEAR IN MATHEMATICS LEARNING AT SDN BANUA ANYAR 4 BANJARMASIN - Hirawatillah, Hijrah; Abdul Aziz, Abdul Rashid; Kamal, Ahlal (Yayasan Maslahatul Ummah Ilal Jannah, 2023)
This study examines the learning difficulties of children with special needs slow lenear in mathematics learning at SDN Banua Anyar 4 Banjarmasin. Departing from the assumption that learning mathematics is very difficult and boring, coupled with the problems that exist in children, namely slow learning and receiving information (slow lenear), it is necessary to study this problem. This research is a field research using qualitative methods with observation, documentation and interview techniques. From this study provides information that the difficulty that often occurs in slow lenear children is difficulty in understanding symbols, distinguishing between letters and numbers, and upper and lower case letters. In addition to the difficulties experienced by students, accompanying teachers also experience several obstacles such as not having media when accompanying students slow lenear learning and lack of accompanying teachers so that they are tired when accompanying students while studying.